THE EFFECT OF EDUCATIONAL BACKGROUND AND LANGUAGE COMPETENCE ON STUDENTS’ ARABIC LANGUAGE MOTIVATION - Mukmin Mukmin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This research was based on the assumption that if a person starts knowing a language from under 12 years of age, he/she will have the opportunity to be able to speak the foreign language as fluent as the native speaker. This research was aimed at determining whether educational background and Arabic language competence influence Arabic language motivation. This research used survey research with a quantitative approach, with the population of PBA students in the academic year 2017/2018. 89 students were chosen as the sample of this research by using purposive sampling technique. Data analysis carried out in this study was normality test, linearity test, multicollinearity test, and heteroscedasticity test. Hypotheses testing include correlation test, regression, t-test, and F-test. The results showed that there was a positive and significant influence of educational background and Arabic language competence on motivation in learning Arabic with the amount of 37.5%. The student background was dominated by students who had known Arabic since early childhood that the students experienced a lateral and positive transfer process.Furthermore, the competencies possessed by students are dominated by students with high competence of 39% of these two variables, obtained by 2 types of motivation, namely intrinsic and extrinsic motivation in Arabic language learning.